Application of standard micro-anatomical staining methods to epoxy resin-embedded sections. Issue 5 (September 1969) - Aparicio, S. R.; Marsden, P.
Abstract : Staining of semi-thin sections of osmium-fixed epoxy resin (Epon or Araldite)-embedded tissues with haematoxylin and acid dyes as counterstains (eosin or phloxin) was successfully achieved after intense oxidation using hydrogen peroxide as the oxygen donor. Results are closely similar to those obtained with paraffin sections (haematoxylin and eosin): nuclei stain blue, cytoplasm and extracellular structures ( eg, collagen, elastica, basement membranes) stain with varying shades of red. Preliminary studies show that similarly good results, comparable with standard paraffinembedded histological materials, can be obtained, using H2 O2 pretreatment, with Weigert's iron haematoxylin, Mallory's phosphotungstic acid haematoxylin, Alcian blue, PAS reaction, Sudan III, Sudan black, oil red, Gomori's aldehyde fuchsin, and Baker's acid haematein.